J S-5 Robots In Pt Matsushita-Toshiba DDI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
ABSTRACT Industrial robots are very much used in manufacturing industries especially in automobile assembling and electronic industries. Its robots is the vertically articulation robots, which are produced by Kawasaki, Panasonic, Fanuc, l'askawa Motoman, Nachi, Kuka, Genio etc. These robots have vertically rotating arms. This paper will discuss about the industrial robots, which is used for painting CRT tube for TV assembling by PT Matsushita-Toshiba Display Device IndOnesia EJIB âLemah abang, Cikarang Jakarta. These Kawasaki JS-5 is a robot has a payload capacity 5 kg , it's used for painting that are very well coordinated with its items. The robot program is very complicated, because of the precision and accuracy are very importance ones and really needed. The kinematics of the arm's rotation is used to solve the operation problems. To solved the base coordinate from the end-effector coordinate can normally use the Denctvit-Hartenberg's formula. The moving from a point to another point can be solved by the best solution e.i inverse kinematics, it is the Euler Angles formula or Paul-Peiper formula etc.